Effect of AlSi coating on laser spot welding of press hardened steel and process improvement with annular stirring. (October 2020) - Chen, Nannan; Wan, Zixuan; Wang, Hui-Ping; Li, Jingjing; Solomon, Joshua; Carlson, Blair E.
Abstract: Laser spot welding method was employed to fabricate AlSi coated press-hardened steel (PHS) joints in overlapped configuration. Al and Si segregate at the notch root of a laser spot weld of AlSi coated PHS resulting in pre-mature cracking and weakening of the joint strength. The thickness-oriented δ-ferrite strips induced by the Al and Si segregation was mainly responsible for the mechanical deterioration though the dispersive δ-ferrite in the fusion zone also contributes. A supplemental annular stirring with beam oscillation is proposed to break up the segregation. With the annular stirring, the lap-shear peak load and energy absorption increased 57% and 80% respectively, which is attributed to the removal of δ-ferrite strips and the reduction in the fraction of dispersive δ-ferrite. Thermo-fluid numerical simulations suggest that the annular stirring promoted the melt flow and extended the duration of the melt pool, which accelerated and prolonged the diffusion of Al and Si atoms into the fusion zone, thus preventing the segregation of Al and Si and formation of δ-ferrite strips. Meanwhile, the prolonged melt flow pulled additional dissolved Al onto the molten pool surface forming the Al oxide film, resulting in further reduction of Al content and fraction of dispersive δ-ferrite. Graphical abstract: Unlabelled Image Highlights: Forming thickness-oriented δ-ferrite strips and dispersive δ-ferrite deteriorated mechanical properties of laser spot welds of press hardened steels An annular welding with beam oscillation was proposed to break up the δ-ferrite strips and reduce the dispersive δ-ferrite. By the developed annular welding, the lap-shear peak load and energy absorption increased 57% and 80%, respectively. Mechanisms of the annular welding in terms of flow and thermal behaviors were revealed by numerical simulations.